Parents' Intention Towards Early Marriage Of Their Daughters In Jambi City: A Cross-Sectional Study From The Perspective Of Social Norms - Fitri, Adelina; Putra, Ashar Nuzulul; Sitanggang, Hendra Dhermawan; Ningsih, Vina Rahayu; Putri, Fitria Eka; Hubaybah, Hubaybah (Jurnal Bidan Cerdas, 2024)
Introduction: Early marriage remains a significant social issue in Indonesia, with adverse economic and health consequences, particularly for young girls. In Jambi Province, the prevalence of early marriage is notably high. Social norms, including parental attitudes, normative expectations, and reference group practices, are critical factors influencing this phenomenon. Objective: This study aimed to analyze the role of social norms in shaping parents' intentions to marry off their daughters at an early age in Jambi City. Methods: A cross-sectional study was conducted among 200 parents using cluster sampling across 11 sub-districts in Jambi City. Data on parental attitudes, empirical and normative expectations, sanctions, and reference group practices were collected through structured questionnaires and analyzed using chi-square tests and multivariate logistic regression. Results: Parental attitudes (OR=4.08, 95% CI: 1.74–9.34, p=0.001), normative expectations (OR=3.62, 95% CI: 1.58–8.28, p=0.003), and reference group practices (OR=2.93, 95% CI: 1.36–6.33, p=0.009) were significantly associated with intentions for early marriage. Multivariate analysis confirmed parental attitudes as the strongest predictor (OR=3.42, 95% CI: 1.46–8.00, p=0.005). Conclusion: Social norms significantly influence parents' intentions to marry off their daughters early. Strategies to mitigate early marriage should focus on educating parents and community leaders, enforcing regulations, and reshaping societal norms to protect adolescents' health and future.